2017
DOI: 10.3126/ajms.v8i5.17771
|View full text |Cite
|
Sign up to set email alerts
|

To evaluate the effects of Nd:YAG laser posterior capsulotomy on best corrected visual acuity (bcva) and intraocular pressure

Abstract: A B S T R A C T ORIGINAL ARTICLE ASIAN JOURNAL OF MEDICAL SCIENCESBackground: Nd: YAG laser is non-invasive and effective means to deal with the posterior capsule opacification. However safe it may have some inherent complications. Rise of intraocular pressure is frequently encountered and incompletely understood complication of YAG laser capsulotomy and documented with conflicting results. Aims and Objective: To assess the efficacy of Nd: YAG laser capsulotomy in term of visual outcome(Best Corrected Visual A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Though, the incidence of 5 mm or above of IOP rise was quite high in the studies conducted in 1980s and 90s 20,21 , the incidence has reduced to a much lower level in the contemporary years. In a 2004 study, Barnes et al 22 reported this incidence to be only 20.7% whereas in a more recent study, Patel et al 23 found IOP rise of >5 mm in only 5% of patients in their study. The reason for relatively lower incidence of IOP rise in our study could also be attributable to a high percentage of patients (58%) receiving topical hypotensive prior to laser procedure.…”
Section: Discussionmentioning
confidence: 87%
“…Though, the incidence of 5 mm or above of IOP rise was quite high in the studies conducted in 1980s and 90s 20,21 , the incidence has reduced to a much lower level in the contemporary years. In a 2004 study, Barnes et al 22 reported this incidence to be only 20.7% whereas in a more recent study, Patel et al 23 found IOP rise of >5 mm in only 5% of patients in their study. The reason for relatively lower incidence of IOP rise in our study could also be attributable to a high percentage of patients (58%) receiving topical hypotensive prior to laser procedure.…”
Section: Discussionmentioning
confidence: 87%
“…The rise in IOP was transient in nature and became normal within 1 week. 15 Another prospective study which was conducted to determine the influence of Nd: YAG laser capsulotomy on various factors like intraocular pressure (IOP), best-corrected visual acuity (BCVA), anterior chamber depth (ACD), pupil depth (PD), central corneal thickness (CCT) and axial length (AL), revealed that there were no significant changes found during the after YAG. 16 In yet another research determining the pre and postoperative IOP after YAG, no substantial difference was seen.…”
Section: Discussionmentioning
confidence: 99%